Pre-clinical evaluation of Fagonia cretica L. extract against CCl4-induced hepatotoxicity in male Wistar Rats - Arshad, Fatima; Altaf, Awais; Arshad, Ali Raza; Maqbool, Tahir; Ashraf, Muhammad Abdul Basit; Akbar, Afsheen (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To investigate the hepatoprotective effects of Fagonia cretica L. (F. cretica) extracts against CCl4-induced hepatotoxicity in rats. METHODOLOGY: The study evaluated the hepatoprotective effects of ethanol and hexane extracts of F. cretica against CCl4-induced liver toxicity in 35 Wistar albino rats divided across five experimental groups. Hepatotoxicity was induced in groups II to V with CCl4, while groups III and IV received plant extracts. Group V was treated with cisplatin, which was used as a standard drug. Alterations in liver damaging and oxidative stress biomarkers were assessed after treatment. RESULTS: The results showed the hepatoprotective effects of EFC (ethanol extract of F. cretica) and HFC (hexane extract of F. cretica) in CCl4 induced hepatotoxicity using male Wistar rats. The extracts demonstrated therapeutic efficacy by normalized liver enzyme levels (ALT, AST). Treatment with plant extracts significantly reduced oxidative stress markers (MDA, NO), while substantially restoring the antioxidative activity of GSH and CAT). Additionally, the extracts effectively downregulated immunological markers (MMP-9 and TGF-?). Histopathological analysis showed enhanced liver regeneration with F. cretica extracts, restoring near normal tissue architecture and minimizing hepatocyte damage and fibrosis. These findings suggest that F. cretica extracts possess potent hepatoprotective effects against chemical-induced liver injury. CONCLUSION: The findings of the study revealed the promising antifibrotic potential of F. cretica extract on liver tissues. Further studies are needed to isolate specific antifibrotic phytochemicals and their cellular targets to advance the treatment options against liver fibrosis and hepatotoxicity.